2018
DOI: 10.1074/jbc.m117.814947
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-specific conformational transitions and intracellular transport are required for atypical chemokine receptor 3–mediated chemokine scavenging

Abstract: The atypical chemokine receptor ACKR3 contributes to chemotaxis by binding, internalizing, and degrading the chemokines CXCL11 and CXCL12 to shape and terminate chemotactic gradients during development and immune responses. Although unable to trigger G protein activation, both ligands activate G protein–independent ACKR3 responses and prompt arrestin recruitment. This offers a model to specifically study ligand-specific receptor conformations leading to G protein–independent signaling and to functional paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 62 publications
2
48
3
Order By: Relevance
“…Moreover, the authors suggest that arrestin binding to ACKR3 is not required for chemokine scavenging. 31 The finding somewhat contrasts other observations where it was shown that CXCL11 and CXCL12 binding to ACKR3 enhances arrestin recruitment. [32][33][34][35][36] A known drawback for the investigations of GPCRs is the paucity of antibodies which recognize endogenous receptors expressed at the cell surface.…”
Section: Introductioncontrasting
confidence: 59%
See 3 more Smart Citations
“…Moreover, the authors suggest that arrestin binding to ACKR3 is not required for chemokine scavenging. 31 The finding somewhat contrasts other observations where it was shown that CXCL11 and CXCL12 binding to ACKR3 enhances arrestin recruitment. [32][33][34][35][36] A known drawback for the investigations of GPCRs is the paucity of antibodies which recognize endogenous receptors expressed at the cell surface.…”
Section: Introductioncontrasting
confidence: 59%
“…CXCL11 induced a faster ACKR3 internalization, but slower recycling than CXCL12. Moreover, the authors suggest that arrestin binding to ACKR3 is not required for chemokine scavenging . The finding somewhat contrasts other observations where it was shown that CXCL11 and CXCL12 binding to ACKR3 enhances arrestin recruitment …”
Section: Introductioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The receptor is then mainly recycled back to the plasma membrane (Luker et al, 2010) even if a partial degradation of ACKR3 can be observed (Hoffmann et al, 2012). Interestingly, Phosphorylation/Interactome Regulate CXCR4/ACKR3 Functions 803 at ASPET Journals on July 3, 2020 molpharm.aspetjournals.org the rate of receptor internalization is faster and recycling is lower in the presence of CXCL11, compared with CXCL12 (Montpas et al, 2018).…”
Section: Downloaded Frommentioning
confidence: 99%